2021
DOI: 10.2217/cer-2020-0141
|View full text |Cite
|
Sign up to set email alerts
|

TELEmedicine as an intervention for sepsis in emergency departments: a multicenter, comparative effectiveness study (TELEvISED Study)

Abstract: Sepsis is a life-threatening infection that affects over 1.7 million Americans annually. Low-volume rural hospitals have worse sepsis outcomes, and emergency department (ED)-based telemedicine (tele-ED) has been one promising strategy for improving rural sepsis care. The objective of this study is to evaluate the impact of tele-ED consultation on sepsis care and outcomes in rural ED patients. The TELEvISED study is a multicenter (n = 25) retrospective propensity-matched comparative effectiveness study of tele-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The TELEmedicine as a Virtual Intervention for Sepsis in Emergency Departments (TELEVISED) study was developed to understand how real-time video consultation is associated with improved guideline adherence and clinical outcomes in rural patients with sepsis. 20,21 An early study showed that telehealth in rural EDs was associated with higher sepsis bundle adherence (adjusted odds ratio [aOR] 17.3, 95% confidence interval [CI] 6.6 to 44.9) 22 , but we subsequently found that one significant barrier to telehealth use was sepsis diagnosis and recognition. 23 In another multicenter study in telehealth-capable hospitals with contemporary controls (n=1,191), we found telehealth consultation was not associated with improved outcomes, but the subgroup of patients treated in the most remote hospitals by advanced practice providers may have had reduced mortality (aOR 0.11, 95% CI 0.02 to 0.73).…”
Section: Importancementioning
confidence: 76%
“…The TELEmedicine as a Virtual Intervention for Sepsis in Emergency Departments (TELEVISED) study was developed to understand how real-time video consultation is associated with improved guideline adherence and clinical outcomes in rural patients with sepsis. 20,21 An early study showed that telehealth in rural EDs was associated with higher sepsis bundle adherence (adjusted odds ratio [aOR] 17.3, 95% confidence interval [CI] 6.6 to 44.9) 22 , but we subsequently found that one significant barrier to telehealth use was sepsis diagnosis and recognition. 23 In another multicenter study in telehealth-capable hospitals with contemporary controls (n=1,191), we found telehealth consultation was not associated with improved outcomes, but the subgroup of patients treated in the most remote hospitals by advanced practice providers may have had reduced mortality (aOR 0.11, 95% CI 0.02 to 0.73).…”
Section: Importancementioning
confidence: 76%
“…The methods of the study have been reported previously (ClinicalTrials.gov NCT04441944), including a detailed description of participating sites. 35 Initially we planned to include 25 hospitals, but two hospitals were excluded because of a lack of data availability ( Supplemental Figure S1 ). This article is reported consistent with the Template for Intervention Description and Replication checklist for Population Health and Policy (TIDieR-PHP), and the study was designed using the Strengthening the Reporting of Observational Studies in the Epidemiology (STROBE) statement.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to avoiding the need for emergency care, as in cases where driving must be outpatient, remote care is helpful to reinforce the need for face-to-face assessment for those who have diseases for which rapid intervention is essential. Finally, for populations that live or work in places far from large centers, for which access to the emergency requires long and/or complex commuting, the initial stages of care can be directed by Telemedicine directly to the patient or between health professionals 19,23,26 .…”
Section: Editorialmentioning
confidence: 99%